Java for beginners : a crash course to learn java programming in 1 week - Ellison, Brady ([United States] : [publisher not identified], 2022)
Java programming is used for many day-to-day applications and is one of the simplest programming languages to learn. You can get the basics down in only one week! This could be the start of a new adventure that can change your life. Knowing how to program Java can allow you to create everything that you always wanted to do.
Introduction -- Chapter 1. Why Java? -- Chapter 2. Variables -- Chapter 3. String Methods -- Chapter 4. Arrays -- Chapter 5. Operators -- Chapter 6. Statements -- Chapter 7. Classes -- Chapter 8. Static Methods and Static Variables -- Chapter 9. Inheritance and Polymorphism -- Chapter 10. Loops -- Chapter 11. Access and scope -- Chapter 12. Debugging -- Chapter 13. Java Files -- Chapter 14. FAQ.
Includes bibliographical references.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)